Melt pool geometry and microstructure of Ti6Al4V with B additions processed by selective laser melting additive manufacturing. (5th December 2019) - He, Yining; Montgomery, Colt; Beuth, Jack; Webler, Bryan
Abstract: This paper documents an investigation into the microstructures and melt pool geometry features of Ti6Al4V + (0, 1, 2, 5, 10, wt%) B alloys processed by selective laser melting (SLM). Single laser-deposited tracks were made on powder-free surface of arc-melted Ti6Al4V-xB buttons. The applicability of powder-free results was supported by evaluation of Ti6Al4V melt pool geometry deposited with and without powder. For each Ti6Al4V-xB composition, melt pools were produced over wide ranges of laser beam power ( P ) and scan speed ( V ), with melt pool geometry and microstructure information gathered into mapping in P-V space to develop P-V process window. By varying wt% B and P-V parameter, a variety of microstructures were produced. A promising microstructure consisted of a TiB network with submicron spacing. Melt pool microhardness was characterized, showing evident enhancement from arc-melted baseline for all Ti6Al4V-xB composition. This work identified Ti6Al4V-xB with 2–5 wt% B as a promising composition range for SLM processing and showed the powder-free methodology can provide melt pool scale information for trial alloy composition evaluation. Graphical abstract: Unlabelled Image Highlights: Boron-added Ti6Al4V-xB alloys processed by selective laser melting (SLM) were evaluated by a powder-free approach. Justification for the powder-free approach was presented using data from Ti6Al4V. Influence of laser power, scan speed and B wt.% on Ti6Al4V-xB melt pool geometry and microstructure were presented. Promising compositions for further study were 2–5 wt% B. Acceptable laser power-scan speed combinations were identified.